Graduación.
Aparecen , de izquierda a derecha María Eugenia Sibaja Solera, Jorge Enrique Guier Esquivel, Ronald García Soto, el Rector - Francisco Antonio Pacheco Fernández entregando un certificado y Enrique Góngora Trejos